Accounting Information System for Cash Receipts and Cash Expenditures at PT Graha Jember Lestari - Hidayat, Syahru; Firdaus, Muhammad Ridwan (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research paper aims to evaluate the accounting information system for cash receipts and expenditures at PT Graha Jember Lestari. It addresses the system's functions, documents, records, and procedures, highlighting the need for a tailored approach to improve management and financial reporting.Method: The study utilizes the Participatory Action Research (PAR) method for data collection and analysis, focusing on current accounting practices and the use of Microsoft Excel and Word for processing cash transactions.Practical Applications: The findings suggest that implementing a more suitable accounting information system can enhance data accuracy and streamline financial reporting, ultimately improving decision-making and efficiency in managing cash flow.Conclusion: The research concludes that PT Graha Jember Lestari must adapt its accounting information system to better meet operational needs. While Microsoft Excel and Word are currently used, they are not optimal for efficient cash transaction processing, highlighting the importance of tailored accounting practices to resolve operational challenges.